Time-space distribution of silicic plutonism in a gneiss dome of the Iberian Variscan Belt: The Évora Massif (Ossa-Morena Zone, Portugal) - Dias da Silva, Í. (2019)
In the Iberian Variscan Belt, polyphasic deformation has been recognized as comprising an early phase of crustal thickening, followed by an intermediate phase of crustal extension and doming, and a later phase of shortening. The Évora Massif is a gneiss dome of the westernmost domains of the Ossa-Morena Zone (SW Iberia), which provides a remarkable insight into the late Paleozoic deep crustal structure of the Variscan continental crust of northern Gondwana. In this study, we bring new structural and geochronological U-Pb data for the northern hanging-wall of the Évora Massif. We describe the existence of low-dipping D2 extensional shear zones associated with Buchan-type metamorphism (M2); this enables three tectono-metamorphic units to be distinguished: the Lower Gneiss Unit, the Intermediate Schist Unit, and the Upper Slate Unit. D2-M2 structures experienced sub- horizontal shortening (D3) and were transposed by low-plunging folding, thrusting and strike-slip faulting. Zircon grains extracted from Pavia quartz-feldspathic gneiss of the Lower Gneiss Unit yielded a crystallization age of ca. 521 Ma (Cambrian Stage 2–3), which establishes a correlation with tectono-metamorphic units of the footwall and southern hanging-wall of the Évora Massif. U-Pb zircon dating of Divôr foliated quartz-diorite (339 ± 7 Ma), Malarranha weakly foliated biotite-rich granite (322 ± 3 Ma), and undeformed porphyritic granite of the Pavia pluton (314 ± 4 Ma) constrain the timing of emplacement of granitic magmas synchro- nously with doming. Carboniferous magmatism initiated with doming (ME1 - ca. 343–335 Ma), continued through D2-M2 (ME2 - ca. 328–319 Ma), and lasted until the waning stage of crustal extension (ME3 - ca. 317–313 Ma). The Évora Massif gneiss dome probably formed as result of the combined effect of gravitational collapse of the thickened crust and buoyancy-driven gravitational instability developed in the partially molten continental crust influenced by the transfer of heat from rising mantle-derived (i.e. dioritic-gabbroic) magmas rocks found in the footwall of the Évora Massif.